Multiscale and Multistep Ordering of Flow-Induced Nucleation of Polymers - Cui, Kunpeng; Ma, Zhe; Tian, Nan; Su, Fengmei; Liu, Dong; Li, Liangbin (Chemical reviews, 2018)
Flow-induced crystallization (FIC) is a typical nonequilibrium phase transition and a core industry subject for the largest group of commercially useful polymeric materials: semicrystalline polymers. A fundamental understanding of FIC can benefit the research of nonequilibrium ordering in matter systems and help to tailor the ultimate properties of polymeric materials. Concerning the crystallization process, flow can accelerate the kinetics by orders of magnitude and induce the formation of oriented crystallites like shish-kebab, which are associated with the major influences of flow on nucleation, that is, raised nucleation density and oriented nuclei. The topic of FIC has been studied for more than half a century. Recently, there have been many developments in experimental approaches, such as synchrotron radiation X-ray scattering, ultrafast X-ray detectors with a time resolution down to the order of milliseconds, and novel laboratory devices to mimic the severe flow field close to real processing conditions. By a combination of these advanced methods, the evolution process of FIC can be revealed more precisely (with higher time resolution and on more length scales) and quantitatively. The new findings are challenging the classical interpretations and theories that were mostly derived from quiescent or mild-flow conditions, and they are triggering the reconsideration of FIC foundations. This review mainly summarizes experimental results, advances in physical understanding, and discussions on the multiscale and multistep nature of oriented nuclei induced by strong flow. The multiscale structures include segmental conformation, packing of conformational ordering, deformation on the whole-chain scale, and macroscopic aggregation of crystallites. The multistep process involves conformation transition, isotropic–nematic transition, density fluctuation (or phase separation), formation of precursors, and shish-kebab crystallites, which are possible ordering processes during nucleation. Furthermore, some theoretical progress and modeling efforts are also included.